Chemoradiation with or without intraoperative radiation therapy in patients with locally recurrent rectal carcinoma - Vincenzo Valentini; A.G. Morganti; Antonio De Franco; Claudio Coco; Carlo Ratto; Gianbattista Doglietto; Lucio Trodella; L. Ziccarelli; Aurelio Picciocchi; Numa Cellini (1999)
BACKGROUND Rectal carcinoma patients with local recurrence are reported to have a dismal prognosis. The purpose of this study was to evaluate the effect of combined modality therapy on clinical outcome and to determine the prognostic impact of a "presurgical" staging system. METHODS Between September 1989 and June 1997, 47 patients (with a median follow-up of 80 months) with locally recurrent, nonmetastatic rectal carcinoma were classified according to the extent of pelvic sidewall involvement as determined by pretreatment computed tomography (CT) scan. They received preoperative external beam radiation (45–47 grays [Gy] in 34 patients; 23.4 Gy in 13 preirradiated patients) plus concomitant 5-fluorouracil (1000 mg/m2/day as a 96-hour continuous infusion on Days 1–4 + 29–32) and mitomycin C (10 mg/m2 as a bolus intravenously on Day 1 + 29). After 4–6 weeks, the patients were evaluated for surgical resection and intraoperative radiation therapy (IORT) procedure (10–15 Gy) or, in unresectable patients, a boost dose was planned by chemoradiation (23.4 Gy) or brachytherapy. Thereafter, adjuvant chemotherapy (5-fluorouracil and leucovorin for a total of six to nine courses) was prescribed. RESULTS During chemoradiation, 2 patients (4.3%) developed Radiation Therapy Oncology Group Grade 3–4 acute toxicity. Twenty-five patients (53.2%) had an objective response after chemoradiation. Twenty-one patients (45%) underwent radical surgical resection. The overall 5-year survival and local control rates were 22% and 32%, respectively. The classification system significantly predicted survival (P = 0.008). Radically resected patients had better local control and survival (P < 0.0001); in patients treated with IORT, the 5-year local control and survival rates were 79% and 41%, respectively. CONCLUSIONS The data from the current study suggest that combined modality therapy was well tolerated and improved resectability, local control, and survival. The classification system appears to be a reliable tool with which to predict clinical outcome in patients with locally recurrent rectal carcinoma. Cancer 1999;86:2612–24. © 1999 American Cancer Society.